2010
DOI: 10.21825/vdt.87440
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcome of conservative treatment in a cat with T9T10 intervertebral disk disease

Abstract: Five days before referral, a 12-year-old male neutered domestic shorthair had developed an acute onset of paraplegia. The cat lived strictly indoors and no known history of trauma or intoxication was reported by the owner. The cat had never displayed similar complaints before and he seemed to be in good general condition. The blood work and thoracic and abdominal radiographs showed no significant abnormalities, except for the narrowing of the intervertebral disk (IVD) space between T9T10 and T10T11. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Signalment was similar across IVDH types, although purebred cats more commonly had a thoracolumbar neuroanatomical localization. Previous literature containing breed data reports that purebred cats account for 30% of IVDH cases (68/229), most frequently Siamese, Persians, and British shorthairs 1–5,8,12–40 . In our study, 34% of cats were purebred, which was not markedly different from the referral population during the study period.…”
Section: Discussionsupporting
confidence: 42%
See 4 more Smart Citations
“…Signalment was similar across IVDH types, although purebred cats more commonly had a thoracolumbar neuroanatomical localization. Previous literature containing breed data reports that purebred cats account for 30% of IVDH cases (68/229), most frequently Siamese, Persians, and British shorthairs 1–5,8,12–40 . In our study, 34% of cats were purebred, which was not markedly different from the referral population during the study period.…”
Section: Discussionsupporting
confidence: 42%
“…Symptomatic IVDHs were located in the thoracolumbar or lumbosacral regions in 86% to 95% of cats in recent studies, 5,8,9 whereas few IVDHs in cats have been reported cranial to the T11 thoracic vertebra (Material S1). As in dogs, several types of IVDH are reported in cats, the majority being intervertebral disc extrusions (IVDE) and protrusions (IVDP) 1–5,8–40 . The prevalence of IVDP in cats is estimated to be high, but many cases can be subclinical 41 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations